Obtaining new feeder cell lines expressing membrane-bound forms of IL-12 and IL-18 to improve the anti-tumor properties of natural killer cells - Mukhametshyna, Nastassia S.; Migas, Alexander A.; Klych, Hanna V.; Lasiukov, Yauheni A.; Shman, Tatsiana V. (Experimental Biology and Biotechnology, 2023)
Numerous clinical studies are currently underway on the use of natural killer cells in the treatment of cancer and solid tumors. However, such immunotherapy may be limited by the short persistence of natural killer cells in the host body and the ability of tumor cells to avoid recognition by natural killer cells. Solving these problems by modifying the initial properties of natural killer cells can significantly increase the effectiveness of antitumor therapy. One of the methods of modification is the use of new feeder cell lines expressing various combinations of membrane-bound cytokines (IL-12, IL-15, IL-18, IL-21) to obtain natural killer cells with a specific phenotype (memory-like). In the course of the work done, two new feeder cell lines based on K-562 cells with ectopic expression of a combination of interleukins IL-15, IL-12, IL-18 and IL-21, IL-12, IL-18 were obtained for the expansion of natural killer cells with enhanced antitumor activity.
Keywords: natural killer cells; interleukins; feeder cell lines; acute leukemia; immunotherapy